(untitled) (Indonesian Art and Justice Review, 2024)
Art has played a crucial role in the formation and expression of Indonesian national identity, particularly in the post-independence era. This paper explores how Indonesian artists, through diverse forms such as painting, sculpture, film, and performance, have contributed to the development of a collective national identity that balances traditional cultural elements with modern influences. The study examines how art reflects the complexities of Indonesia’s multicultural society, addresses issues of unity and diversity, and negotiates between local, regional, and national identities. By analyzing key artistic movements and influential works, this paper argues that art not only reflects national identity but actively shapes it, offering a space for contestation and reaffirmation of what it means to be Indonesian.